Development of a porous, biphasic, resorbable osteochondral scaffold for the functional regeneration of osteochondral lesions - Pitrolino, Katherine (2020)
Tissue engineering and regenerative medicine research investigate the ability to repair and restore function in the body using biological cells, signals or biomimetic scaffolds. In particular, bone and cartilage tissue engineering has led to the development of many products reaching clinical trials and some obtaining regulatory approval as a class III medical device. Unfortunately, despite a large effort by researchers and industry, there is a lack of cost effective and scalable treatments to regenerate and restore function in an osteochondral defect.